Comprehensive Evaluation of Non-invasive Prenatal Screening to Detect Fetal Copy Number Variations - Wang, Jing; Zhang, Bin; Zhou, Lingna; Zhou, Qin; Chen, Yingping; Yu, Bin (Frontiers in Genetics, 2021)
Objective: To evaluate the effectiveness of noninvasive prenatal testing (NIPS) in prenatal screening of fetal pathogenic copy number variants (CNVs). Methods: We evaluated the prenatal screening capacity using the traditional process in which24613 pregnant women underwent NIPSand womenwith suspected fetal CNVs received prenatal diagnosis with chromosomal microarray analysis (CMA). We compared this process witha retrospective process in which47 cases with fetal pathogenic CNVs were retrospectively analyzed for NIPS. Asystematic literature search was also performed to evaluatethe efficiencies of these methods. Results: Among the 24613 pregnantwomen who received NIPS, 124 (0.50%) were suspectedto have fetal CNVs. Of these, 66 women underwent prenatal diagnosis with CMA and13 had true positive results. The positive predictivevalue (PPV) of NIPS for fetal CNVs was 19.7%. Among 1161 women who underwentprenatal diagnosis by CMA, 47 (who did not receive NIPS) were confirmed to havefetal pathogenic CNVs. Retesting with NIPS indicated that 24 of these 47 cases could also be detected by NIPS, representing a detection rate (DR) of 51.1%. However, the remaining 23 cases could not be detected by NIPS, and the false-negative rate (FNR) was 48.9%. Intotal, 10 publications, including six retrospective studies and four prospective studies, metour criteria and were selected for a detailed full-text review.The reported DRs were 61.10–97.70% and the PPVs were 36.11–80.56%. The sizes of CNVs were closely related to the accuracy of NIPS detection. The DR was 41.9% (13/31) in fetuses with CNVs < 3 Mb, but was55.0% (11/20) in fetuses withCNVs > 3Mb. Finally, to intuitively show the CNVs accurately detected by NIPS, we mapped all CNVs to chromosomes according to theirlocation, size,and characteristics. NIPS detected all of fetal CNVs in 2q13 and 4q35. Conclusions: The DR and PPV of NIPS for fetal CNVs were approximately 51.1% and19.7%, respectively.Follow-up molecular prenatal diagnosis is recommended in cases whereNIPS suggests fetal CNVs.